Curriculum re-engineering: Implications for technological empowerment and job creation tendencies among secondary school students in Cross Rivers State, Nigeria (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This study examined curriculum re-engineering, technological empowerment and job creation tendencies among secondary school students. The aim was to investigate the extent to which curriculum re-engineering is likely to promote technological empowerment and enhance job creation tendencies among secondary school students. Exploratory survey research design was adopted for the study, 2 research questions were raised to direct the study. The population of the study comprised all the 281 public secondary schools in Cross River State. Multi-stagesample procedure was used to select 9 public secondary schools as sample schools for this study. The instrument for data collection was a self-structured questionnaire titled "Curriculum Re-engineering for Technological Empowerment and Job Creation Tendencies Survey (CRTEJTS). The CVI of the instrument ranged between 0.72 and 0.87, while the reliability estimates of the research instrument ranged from .82 and .89. Descriptive statistics (simple percentages, mean and standard deviation) were used to answer the research questions. The result of the study revealed that curriculum re-engineering is likely to promote technological empowerment among secondary schools students and arouse job creation tendencies in them. It was therefore recommended that secondary school curriculum should re-organized to ensure full application of ICT tools in the teaching and learning process, and hat teachers and students should be allowed to explore all available e-learning platforms in the process of teaching and learning, as this will empower students technological and arouse job creation attributes among them.
Keywords: Curriculum re-engineering; technological empowermen; job creation; job creation tendencies; self-efficacy; self-reliance